A Study of Loyalty Programs on Customer Engagement for Bluestone Jewellery and Lifestyle Pvt Ltd. With Special Reference to The Shivranjani Store in Ahmedabad City - Hitiksha Lodhiya; Yash Jangid; Jignesh Vidani (Journal of Advanced Research in Entrepreneurship, Innovation and SMES Management, 2024)
Bluestone’s Shivranjani store in Ahmedabad faces a challenge: declining customer engagement and a loyalty program seemingly falling short. Limited customization, inflexible rewards, and unclear mechanics might be driving customers to competitors offering more appealing deals and clearer value propositions. This study dives into the competitive landscape, analyzing what rivals offer and how it resonates with Ahmedabad’s diverse customer segments. By understanding the reasons behind Bluestone’s customer churn, we can determine if strategic program adjustments or innovative marketing campaigns are needed to retain existing customers and attract new ones. Through a descriptive research design and surveys distributed to 105 local customers, the study delves into program specifics, customer demographics, and overall perception. Using statistics like frequencies and percentages, the analysis aims to unveil the program’s weaknesses and identify areas for improvement. Armed with these insights, we can tailor recommendations for program refinement and marketing strategies to reignite customer engagement and establish Bluestone as the premier jewellery destination in Ahmedabad. The study found Bluestone’s loyalty program has boosted engagement at the Shivranjani store. Customer demographics lean towards young women, and most purchase gold occasionally. Bluestone holds 34% of the market share, followed by local stores at 39%. Interestingly, 69% are GMS plan users, yet over half are unaware of its details. However, 74% are overall satisfied and recommend the program, with GMS users particularly positive. While 46% aren’t interested in any loyalty program, feedback suggests Bluestone can strengthen GMS by increasing first instalment discounts and addressing making charges. Overall, the research points to potential for further program refinement and market leadership.